Causal effect of the outsourcing of library management on public library usage in Japan - Tsuji, Keita (2022)
Background. For a long time, Japanese public libraries were managed by local governments. However, in 2003, other organizations, including private enterprises, took over the management of libraries and introduced an outsourcing system called designated administrator system. The suitability of this outsourcing system for libraries is now being debated. Objective. We conducted a causal analysis on the introduction of outsourcing in public libraries in Japan. We performed matching analysis, difference-in-differences (DD) analysis, and DD analysis with matching on library usage, in terms of three factors—gate count, number of loans, and number of reference transactions. Results. The matching analysis found that the average gate count per capita for all outsourcing libraries was higher than that for all direct management libraries. In the DD analysis with and without matching, the average gate count per capita and number of loans per capita for all the outsourcing libraries were higher than for all the direct management libraries. These differences were statistically significant at the 0.01 level. Conclusion. The results indicate that the introduction of the designated administrator system increases gate count per capita. Considering the difference in characteristics of the matching and DD analyses, the number of loans per capita may also be increasing with the introduction of the system.